Removal of fluoride from wastewater using HCl-treated activated alumina in a ribbed hydrocyclone separator. Issue 7 (7th June 2018) - Patra, Gayatree; Das, Priyam; Chakraborty, S.; Meikap, B. C.
ABSTRACT: Excessive fluoride concentration in wastewater is a major health concern worldwide. The main objective of wastewater treatment is to allow industrial effluents to be disposed of without danger to the human health and the natural environment. In this current study, experiments have been conducted to remove fluoride from aqueous solution using alumina and HCl (Hydrochloric acid) treated activated alumina in a continuous mode. A spiral rib was introduced in the cylindrical part of the conventional hydrocyclone to increase the performance, and the new hydrocyclone is dubbed as ribbed hydrocyclone. Experiments were carried out to analyze the performance of the ribbed hydrocyclone and compared the results with the conventional hydrocyclone of the same dimension. The efficiency of conventional and ribbed hydrocyclone at a slurry flow rate of 50 LPM (liter per minute) for the solid concentration of 1.4 wt% were 80% and 93.5% respectively. The cut size d50 of the conventional and ribbed hydrocyclone was 18 µm and 13 µm respectively at a slurry velocity of 50 LPM. Fluoride removal efficiency using alumina and HCl-treated alumina was also investigated in a continuous mode by the ribbed hydrocyclone. Maximum fluoride removal efficiency was 49.5%, and 80% for alumina and HCl-treated alumina for the initial concentration of 10 mg/L at a slurry flow rate of 50 LPM.